Strigolactone‐triggered stomatal closure requires hydrogen peroxide synthesis and nitric oxide production in an abscisic acid‐independent manner. Issue 1 (22nd September 2017) - Lv, Shuo; Zhang, Yonghong; Li, Chen; Liu, Zhijun; Yang, Nan; Pan, Lixia; Wu, Jinbin; Wang, Jiajing; Yang, Jingwei; Lv, Yanting; Zhang, Yutao; Jiang, Wenqian; et al.
Summary: Accumulating data indicate that strigolactones (SLs) are implicated in the response to environmental stress, implying a potential effect of SLs on stomatal response and thus stress acclimatization. In this study, we investigated the molecular mechanism underlying the effect of SLs on stomatal response and their interrelation with abscisic acid (ABA) signaling. The impact of SLs on the stomatal response was investigated by conducting SL‐feeding experiments and by analyzing SL‐related mutants. The involvement of endogenous ABA and ABA‐signaling components in SL‐mediated stomatal closure was physiologically evaluated using genetic mutants. Pharmacological and genetic approaches were employed to examine hydrogen peroxide (H2 O2 ) and nitric oxide (NO) production. SL‐related mutants exhibited larger stomatal apertures, while exogenous SLs were able to induce stomatal closure and rescue the more widely opening stomata of SL‐deficient mutants. The SL‐biosynthetic genes were induced by abiotic stress in shoot tissues. Disruption of ABA‐biosynthetic genes, as well as genes that function in guard cell ABA signaling, resulted in no impairment in SL‐mediated stomatal response. However, disruption of MORE AXILLARY GROWTH2 ( MAX2 ), DWARF14 ( D14 ), and the anion channel gene SLOW ANION CHANNEL‐ASSOCIATED 1 (SLAC1) impaired SL‐triggered stomatal closure. SLs stimulated a marked increase in H2 O2 and NO contents, which is required for stomatal closure. Our results suggest that SLs play a prominent role, together with H2 O2 /NO production and SLAC1 activation, in inducing stomatal closure in an ABA‐independent mechanism.